Analysis of Changes in Flow Setting Against Rise Time Using Gas Board 7500E Sensor on Bubble CPAP - Pudji, Andjar; Amrinsani, Farid; Luthfiyah, Sari; Lusiana, Lusiana; Misra, Shubhrojit; Ahniar, Nur Hasanah; Barus, Yenda Mita; Lamidi , Lamidi (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Respiratory distress syndrome (RDS) is a breathing disorder that occurs in newborns, often in premature babies born before 28 weeks of gestation. The bubble CPAP (Continuous Positive Airways Pressure) is a device used to provide positive pressure to newborns who can breathe spontaneously but are still prone to apnoea. The rise time is the time it takes for the airway pressure to reach the maximum standard value. The aim of this study is to analyze the changes in flow regulation during the rise time using a 7500E gas sensor card on a bubble CPAP probe. The method used in this study is to use the mean hijacking of the sensor to reduce the noise generated by the sensor. When analyzing the data, the researcher recorded data up to five times and calculated the mean measurement error. The research design is calibrated to confirm the correctness of the displayed values. The results of the data analysis are a mean error value of 0.88% at a setting of 30% oxygen content, 0.78% at a setting of 50%, and 0.95% at a setting of 90%. For liters per minute (LPM) at the 1 LPM and 5 LPM settings, the mean error values are 0.18 % and 0.03 % for the 10 LPM setting. From the test results with 3 bubble CPAP devices, it appears that when a high LPM setting is used, the oxygen concentration is reached faster with a mean value of ±10 seconds. The conclusion from this study shows that increasing the oxygen flow rate affects the duration of the rise in bubble CPAP oxygen concentration. The implication of this study is that this data will help add artificial intelligence to bubble CPAP to automatically determine settings by combining breathing data from patients.